2005
DOI: 10.1002/art.20762
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid levels and serum pharmacokinetics in a large animal model following treatment with oral glucosamine at clinically relevant doses

Abstract: Objective. To examine the concentration of glucosamine in the synovial fluid and its pharmacokinetics in serum in a large animal model following dosing with glucosamine HCl at clinically relevant levels.Methods. Eight adult female horses were studied. After an overnight fast, glucosamine HCl (20 mg/kg of body weight) was administered by either nasogastric (NG) intubation or intravenous (IV) injection. Blood samples were collected before dosing and at 5, 15, 30, 60, 120, 180, 240, 360, 480, and 720 minutes afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 55 publications
1
115
1
7
Order By: Relevance
“…This may explain previous observations by Laverty et al that show only ~10% increase of glucosamine concentration in synovial joint fluid was found following intravenous (IV) or nasogastric (NG) dosing as compared to serum concentrations (Meulyzer et al, 2008). This bioavailability was deemed to be insufficient to cause any improvement in cellular expressions or metabolic activity as demonstrated by others (Laverty et al, 2005;Meulyzer et al, 2008). For in vivo effects of glucosamine on chondrocytes to be significant, it has been demonstrated that the monosaccharide component of GS would have to "accumulate" in cartilage to levels at least 500 times higher than those present in the synovial fluid of patients receiving therapeutic dosages (Laverty et al, 2005;Meulyzer et al, 2008).…”
Section: T Kamarul Et Al Surgically Treated and Untreated Focal Cartmentioning
confidence: 67%
See 3 more Smart Citations
“…This may explain previous observations by Laverty et al that show only ~10% increase of glucosamine concentration in synovial joint fluid was found following intravenous (IV) or nasogastric (NG) dosing as compared to serum concentrations (Meulyzer et al, 2008). This bioavailability was deemed to be insufficient to cause any improvement in cellular expressions or metabolic activity as demonstrated by others (Laverty et al, 2005;Meulyzer et al, 2008). For in vivo effects of glucosamine on chondrocytes to be significant, it has been demonstrated that the monosaccharide component of GS would have to "accumulate" in cartilage to levels at least 500 times higher than those present in the synovial fluid of patients receiving therapeutic dosages (Laverty et al, 2005;Meulyzer et al, 2008).…”
Section: T Kamarul Et Al Surgically Treated and Untreated Focal Cartmentioning
confidence: 67%
“…past, the roles of these supplements have been queried, particularly in relation to whether direct metabolism can, in effect, aid the increase in production of cartilage proteoglycan sub-units (Laverty et al, 2005). Furthermore, it is also unclear how oral GS and CS reach the defective or repaired sites considering that cartilage itself is avascular (O'Driscoll, 1998;Bentley et al, 2003;Piasecki et al, 2003;Shelbourne et al, 2003).…”
Section: T Kamarul Et Al Surgically Treated and Untreated Focal Cartmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacokinetics of various solutes have been examined in a wide range of species from animals as large as horses [1,2] to sheep [3,4], dogs [5,6], rabbits [7][8][9] and finally to animals as small as rats and mice [10,11]. Apart from inherent inter-and intra-species differences in cell type, tissue composition and mechanical properties, there is a huge difference between the disc sizes among these species.…”
Section: Introductionmentioning
confidence: 99%